Evaluation of the Effect of Sand Pack Coverings on Rockfall Protection Fences Using Numerical Approach. Issue 2 (June 2014) - Ho, Tam Sy; Masuya, Hiroshi; Nishita, Youichi
Flexible fences have been used widely for protection against rockfall impact and have garnered considerable attention from engineers and researchers due to their effectiveness and adaptability to various types of topography and impact energy magnitude. Generally, friction braking devices are widely used for absorbing impact energy and external support cables are added to enhance structure stability. The utilization of sand packs as impact absorbing components in the fence structure is considered a new and rational idea. This research was conducted to gain better understanding of the structural behavior of a fence without any braking device or external support cable, and the absorption performance of sand pack to cushion rockfall impact. The fence studied in this research consist of three spans of cable net covered by 14 sand packs, and was subjected to impact load by a vertical free fall of weight. The sand packs covering the fence were considered for a numerical study using the finite element method of LS-DYNA to simulate the behavior of the complete fence structure, including the sand pack cushion. The numerical model was adequately validated through a comparison between the results of the model analysis and those of the fundamental experiment. The examination and discussion of the structural dynamic behavior of fences by applying the validated model clearly revealed the effects of the sand pack and impact energy magnitudes on the structural characteristics of the fence. These effects led to the revelation that the absorption performance of the sand pack coverings to absorb the impact and redistribute its load are expected to result in the practical application of sand packs as absorbing elements in rockfall protection fences.